ORGANISASI GERAKAN SOSIAL (STUDI : SERIKAT TANI RIAU DALAM MENGADVOKASI KEPENTINGAN MASYARAKAT PULAU PADANG) - Yoshep Saputra; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study used a qualitative descriptive method. Research location in the village of Padang Island District of Merbau Meranti Islands District to focus research on the conflict between Padang and PT Society Islands. RAPP, In 2009 PT.RAPP have obtained the addition or expansion of Utilization License Timber Forest Products Forest Plants (IUPHHK-HT) through Decree SK.327 / Menhut-II / 2009 on June 12, 2009 covering an area of 115 025 ha. So when this area of PT.RAPP is 350 165 hectares, including an area of 41 205 hectares ereal located on the island of Padang. 41 205 hectares of land is the one who in the community problem in Padang IslandBased on research conducted by the authors of the Conflict Padang Island, people refuse beroprasinya PT.RAPP in Padang Island neighborhood by performing various kinds of protest to the company up to the central government. As for the actions that are carried out demonstrations, mouth sewing action, the action of self-immolation threat to the President, Establishment of the monument as a form of rejection PT.RAPP in Pulau Padang.;. Solutions conflict settlement between the company PT.RAPP is already in promise promised by the government such as conciliation and mediation. But the events that have occurred since the end of 2009 until today has not been resolved and have not found a point he explained.Riau Farmers Union (STR) plays an important role in the fight for rights - the rights of farmers Riau specifically concerning the conflict this Padang Island, as for the efforts that have been made in the fight and advocate STR Padang Island community by performing radicalization, Expansion Structure / Branches and Building Unity - Unity (front - front) Democratic.Keyword: Social Organisation, Social Conflict, Pulau Padang